Phytogenic Silver Nanoparticles from Callicarpa macrophylla and their Biological Activities - H.K. Ranjini; K. Manju; H. Shayista; S. Niranjan Raj; Syed Baker; Ashwini Prasad (Journal of Pure and Applied Microbiology)
In the present investigation, the phytogenic synthesis of silver nanoparticles (AgNPs) was carried out with Callicarpa macrophylla which possess multiple functional properties. The absorbance peak of the resultant AgNPs was found to be between 300 and 800 nm, with the highest absorbance at 436 nm. The phytocomponents accountable for facilitating the synthesis were determined through the utilization of Fourier-transform infrared (FTIR) analysis, which unveiled the presence of hydroxyl, amide, aldehyde, and alkene moieties. The crystal structure of the AgNPs was investigated via X-ray diffraction (XRD) analysis, which exhibited diffraction intensities at the 2-theta angle, signifying the presence of a well-defined crystalline structure of AgNPs. The polydispersity of the AgNPs was observed under a transmission electron microscope (TEM), with an average particle size of 10 to 60 nm. The AgNPs exhibited moderate antibacterial activity against Pseudomonas aeruginosa, Escherichia coli, Staphylococcus aureus. The sprouting percentage of Pisum sativum, Vigna radiata, and Macrotyloma uniflorum seeds was assessed with notable observation of increase in length of root size was maximum at AgNPs concentrations of 5 mg/mL and 2 mg/mL for Pisum sativum and Vigna radiata, respectively. However, in the case of Macrotyloma uniflorum, the highest germination rate was observed at a concentration of 10 mg/mL. Similarly, shoot length was highest in all seeds at 10 mg/mL. Furthermore, the AgNPs showed significant dye degradation capabilities, with the highest degradation rate for safranin (58%), followed by methylene blue (35%), and the least degradation observed with crystal violet (21%). Overall, the studies confirm the multi applicative properties of AgNPs synthesized from Callicarpa macrophylla.